Utilization of Pictures Story Media Using the Story Jumper Platform to Instill Pancasila Values - Roso Murti; Shaleh Shaleh; Fina Hanifa Hidayati (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to examine the use of online illustrated stories using the storyjumper platform as a medium for instilling Pancasila values in undergraduate students of the Mathematics Education Study Program at Sunan Kalijaga University. The method used in this research is a descriptive qualitative research method which aims to understand the phenomenon of the implementation and evaluation plans of the study program in instilling Pancasila values through the media of illustrated stories. The results of this research are that the use of ICT-based picture story learning media, besides being fun, is also able to provide learning motivation, especially for students. Storyjumper, which is a type of learning application that utilizes this technology, contributes to the creation of illustrated stories that instill Pancasila values. Although in practice, students experience several obstacles in terms of using the platform, solutions can be found. Choosing picture stories in learning is one of the media used by students because it has many positive values or advantages. Among the advantages of this media are that it is easy and flexible; cheap and economical; increasing student creativity; help and provide insight into the values of Pancasila